Knowledge, Attitudes and Practices (KAP) Study on Household Solid Waste Management among Urban and Rural Homemakers in Kerala - Treesa Sindhu P. Thomas & Dr. Leena Leon (South Eastern European Journal of Public Health, 2025)
This study examines the knowledge, attitude, and practices (KAP) of urban and rural homemakers in Kerala regarding household solid waste management (SWM). With rapid urbanization and increasing environmental concerns, effective waste management has emerged as a critical issue in the state. The research aims to assess the understanding, attitudes, and behaviors related to solid waste management among households. Using a mixed-methods approach, the study collected data from 526 homemakers through a survey. The findings revealed that 51.7% of participants exhibited moderate knowledge, while 83.8% demonstrated positive attitudes towards solid waste management. Significant differences were observed between urban and rural homemakers in terms of knowledge, waste segregation practices, and disposal methods. Rural homemakers predominantly relied on traditional methods such as composting and burning waste, with lower participation in formal segregation programs. Despite favorable attitudes toward SWM, challenges such as inadequate infrastructure, limited recycling facilities, and space constraints remain, particularly in rural areas. The study highlights the need for targeted awareness campaigns, enhanced infrastructure, and community-driven solutions to foster sustainable waste management practices across both urban and rural regions of Kerala.